Schoenberg's musical imagination - Cherlin, Michael (Cambridge ; New York : Cambridge University Press, 2007)
No composer was more responsible for changes in the landscape of twentieth century music than Arnold Schoenberg (1874-1951), and no other composer's music inspired a commensurate quantity and quality of technical description. Yet there is still little understanding of the correlations between Schoenberg's musical thought and larger questions of cultural significance in and since his time: the formalistic descriptions of music theory do not generally engage larger questions in the history of ideas, and scholars without an understanding of the formidable musical technique are ill-equipped to understand the music Schoenberg's Musical Imagination is intended to connect Schoenberg's music and critical writings to a larger world of ideas. While most technical studies of Schoenberg's music are limited to a single compositional period, this book traces changes in his attitudes as a composer, and their impact on his ever-changing compositional style over the course of this remarkable career.
A passing of worlds: Gurrelieder as Schoenberg's reluctant farewell to the nineteenth century -- Dialectical opposition in Schoenberg's music and thought -- Dramatic conflict in Pelleas und Melisande -- Motive and memory in Schoenberg's First string quartet -- Uncanny expressions of time in the music of Arnold Schoenberg -- The tone row as the source of dramatic conflict in Moses und Aron -- The String trio : metaleptic Schoenberg.
Includes bibliographical references (pages 384-389) and indexes.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Schoenberg, Arnold, -- 1874-1951 -- Criticism and interpretation; Schoenberg, Arnold, -- 1874-1951; Schönberg, Arnold -- 1874-1951; Schönberg, Arnold; BIOGRAPHY & AUTOBIOGRAPHY -- Composers & Musicians; MUSIC -- Individual Composer & Musician; Muziekwerken; Electronic book; Criticism, interpretation, etc